Computer games and software engineering - Cooper, Kendra M. L.; Scacchi, Walt (Chapman & Hall/CRC innovations in software engineering and software development., 2015)
Computer games represent a significant software application domain for innovative research in software engineering techniques and technologies. Game developers, whether focusing on entertainment-market opportunities or game-based applications in non-entertainment domains, thus share a common interest with software engineers and developers on how to best engineer game software. Featuring contributions from leading experts in software engineering, the book provides a comprehensive introduction to computer game software development that includes its history as well as emerging research on the inte.